(untitled) (International relations and international law Journal, 2020)
The article is written in the genre of a political portrait and is dedicated to the leader of the Vietnamese people and the first President of the Democratic Republ+ic of Vietnam (DRV) Ho Chi Minh, as well as to the topic of relations with the USSR. The author traces the evolution of his understanding and assessment of Soviet-Vietnamese relations, which naturally led to the approval of close cooperation between the countries at that time. The analysis of the facts from the domestic press and different political examples vividly show that relations with Vietnam during the life of Ho Chi Minh had a long and positive history. The author highlights the specifics of friendly and constructive contacts between the two countries in the context of the development of integration ties between the states at all levels. The author comes to the conclusion, that comprehensive strategic cooperation between Russia and Vietnam is a powerful factor of stability in the Asian continent. Key words: Ho Chi Minh, Vietnam, visit to the USSR, Soviet-Vietnamese relations, strategic partnership.